Phase behaviour of essential oil components in supercritical carbon dioxide - Akgün, M; Akgün, NA; Dinçer, S (ELSEVIER SCIENCE BV, 1999)
The vapour-liquid equilibria of alpha-pinene, limonene and fenchone, and solubility behaviour of camphor were measured in supercritical carbon dioxide (SC-CO2) as a function of pressure and temperature using the static method. Experiments were carried out in the temperature range of 313-333 K and in the pressure range of 6-13 MPa. Experimental results were correlated by the Peng-Robinson equation of stale using conventional mixing rules with one interaction parameter. (C) 1999 Elsevier Science B.V. All rights reserved.
Keywords: camphor; fenchone; limonene; alpha-pinene; phase behaviour; solubility; supercritical fluids; VAPOR-LIQUID-EQUILIBRIA; FLUID EXTRACTION; PLUS LIMONENE; MIXTURES; Chemistry; Engineering